Analysis and Evaluation of Hydrogeological Condition in Jingxin Mining Area - Xing, Yannan (International Journal of Natural Resources and Environmental Studies, 2026)
This study a systematic analysis on the hydrogeological conditions of Jingxin mining area to prevent water inrush accidents in coal mine shafts. Based on industry norms such as the "Mine Water Prevention Detailed Rules" and the "Procedures for the Layout and Pressure Mining of Coal Pillars and Water Bodies in Buildings, Water Bodies, Railways and Main Shaft and Tunnel Coal Pillars", the key elements such as the aquifers and water bodies affected or damaged by mining in the mining area, the distribution of old void water in the mining area and surrounding areas, the mine water inflow volume, the water inrush volume during mine outbursts, and the difficulty of water prevention and control were analyzed. The mine hydrogeological type was determined. In addition, the height of the water-conducting fracture zone of the coal seam and the water volume in the abandoned area were calculated using relevant formulas. Through analysis and calculation, it was concluded that the aquifers and water bodies affected or damaged by the current mining coal seam in the mining area are the overlying Lower Shizheji Formation and the sandstone fracture aquifers of the Shanxi Formation; most areas of the water-conducting fracture zone of the No. 3 coal seam can reach the surface, and the surface of the working face during mining can form ground cracks, and the mine water inflow volume is affected by atmospheric precipitation and surface water during the rainy season, and they are positively correlated with each other. Although it has an impact on mining, it is generally controllable, and the difficulty of water prevention and control is relatively low. On this basis, targeted water prevention and control suggestions were proposed in accordance with the "Regulations on Mine Geological Work".